2003
DOI: 10.1136/jcp.56.7.507
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of nuclear expression of the p33ING1b inhibitor of growth protein in invasive carcinoma of the breast

Abstract: Background/Aims: The inhibitor of growth gene 1 (ING1) is a modulator of cell cycle checkpoints, apoptosis, and cellular senescence. The most widely expressed ING1 isoform is p33ING1b , which can modulate p53, a molecule that is frequently altered in breast cancer. Reduced ING1 mRNA expression has been observed in primary breast cancer expressing wild-type p53. Methods: p33ING1b , p53, oestrogen receptor (ER), and progesterone receptor (PgR) expression was studied in 86 primary invasive breast cancers using im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…ING1b expression was down-regulated in the gastric adenocarcinoma cell lines SGC-7901, MKN28, and MKN45 compared with the normal by nucleus-to-cytoplasm translocation in cancer cells [11,22]. Based on these results, it can be concluded that decreased expression of p33 ING1b is a common phenomenon in gastric adenocarcinoma, and this alteration might contribute to the development of gastric adenocarcinoma.…”
Section: P33mentioning
confidence: 62%
See 1 more Smart Citation
“…ING1b expression was down-regulated in the gastric adenocarcinoma cell lines SGC-7901, MKN28, and MKN45 compared with the normal by nucleus-to-cytoplasm translocation in cancer cells [11,22]. Based on these results, it can be concluded that decreased expression of p33 ING1b is a common phenomenon in gastric adenocarcinoma, and this alteration might contribute to the development of gastric adenocarcinoma.…”
Section: P33mentioning
confidence: 62%
“…Based on reports of malignancies in the stomach [7], esophagus [8], brain [9], breast [10], blood [11,12], lung [13], liver [14], head and neck [15], lymphoid system [16], thyroid [17], and ovary [18], it can be deduced that the expression of p33…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies used primers for mRNA expression analysis An interesting finding is that one group showed the downregulation of nuclear expression of the p33ING1b protein in invasive carcinoma of the breast, acute lymphoblastic leukemia, and melanocytic lesions [55][56][57] . Reduced nuclear expression of p33ING1b both in intensity and in the proportion of cells stained was associated with enhanced cytoplasmic p33ING1b expression in a subset of cases.…”
Section: Deregulation Of Ing Family Genes In Tumorsmentioning
confidence: 99%
“…To date, inactivation and/or decreased expression of p33 ING1b have been reported in various types of cancer, including head and neck squamous cell, breast, lung, stomach, blood and brain malignancies (7,(12)(13)(14)(15)(16). To the best of our knowledge, although there are a few studies of p33…”
Section: Previous Studies Have Shown That P33mentioning
confidence: 98%